2006
DOI: 10.1029/2006gl026835
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical model of electrokinetic potential response during hydrocarbon recovery

Abstract: We present results from a new numerical model capable of simulating two‐phase flow in a porous medium and the electrical potentials arising due to electrokinetic phenomena. We suggest that, during water‐flood of an initially oil‐filled reservoir, encroaching water causes changes in the electrokinetic potential at the production well which could be resolved above background electrical noise; indeed, water approaching the well could be detected several 10's to 100's of meters away. The magnitude of the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 16 publications
2
47
0
Order By: Relevance
“…With the factor F given above, we find that C in agreement with the data in [6]. 7 10 /  = 0.86 VP a…”
Section: Electrokinetic Coupling Coefficientssupporting
confidence: 77%
See 1 more Smart Citation
“…With the factor F given above, we find that C in agreement with the data in [6]. 7 10 /  = 0.86 VP a…”
Section: Electrokinetic Coupling Coefficientssupporting
confidence: 77%
“…Hydrogeological applications concern the study of water leakage from dams [1], groundwater flows in geothermal fields and volcanoes [2], estimation of water resources [3]. In electrochemistry, the above equation form a basis for managing microchip separations of analytes in nano-channels [4]; there is also an evidence that this equation find applications in hydrocarbon recovery [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This formulation avoids the introduction of the zeta potential in describing the electrokinetic properties of porous media as done in most alternative models [3][4][5][6][7]. Our formulation emphasizes the role of the velocity of the water phase in playing a key-role in the electrokinetic properties of the porous material rather than focusing on the pressure field of the water phase.…”
Section: Volume-averaging the Streaming Current Densitymentioning
confidence: 99%
“…In geosciences, examples include water transport in unsaturated parts of the porous soils [3,4,5], monitoring of the oil / water interface in reservoir engineering [6,7], remediation (by electro-osmotic pumping) of soils contaminated by nonaqueous phase liquids (NAPLs) [8], monitoring of CO 2 sequenstration in the ground, healing of cracks of unsaturated clay-rocks by electro-osmotic pumping in civil engineering, and the study of diffusion of ionic species in unsaturated clay-rocks used as host formations for long-term storage of toxic wastes. To the best of our knowledge, our model is the first rigorous attempt to derive the governing equations that describe the effect of water saturation upon streaming potential and electro-osmosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical modeling work has suggested that measurements of streaming potential, acquired using electrodes permanently installed downhole, could be used to monitor water saturation changes in the vicinity of a well during oil or gas production (Saunders et al, 2006(Saunders et al, , 2008. The streaming potential is due to inflow of water to the reservoir as the hydrocarbons are extracted, either from an underlying aquifer or from water injection wells.…”
Section: Introductionmentioning
confidence: 99%